Analisis Semiotika Nilai-Nilai Edukasi Dalam Lagu Berencana Itu Keren - Pohan, Syafruddin; Pratiwi, Nurhasanah (Fakultas Agama Islam Universitas Billfath, 2022)
This paper aims to specifically reveal the signs in the form of educational values contained in the song